1998
DOI: 10.1021/jp982965z
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Adsorption of Simple Linear Alkane Mixtures onto Graphite

Abstract: The combination of differential scanning calorimetry and incoherent elastic neutron scattering has been used to demonstrate the formation of solid layers adsorbed onto graphite from pure alkanes and binary alkane mixtures. We report enthalpies and temperatures of the monolayer transitions for pure alkanes and mixtures and note that the solid monolayers melt at approximately 1.1 times the melting point of the bulk liquid or solution. In the mixtures the longer alkane is found to be preferentially adsorbed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 11 publications
6
66
2
Order By: Relevance
“…For the composition with a higher percentage of methane, the fluctuation characteristics of the density profile compare well with results from previous studies related to pure methane adsorption (Ambrose et al, 2012;Liu et al, 2013;Mosher et al, 2013). Owing to the adsorption propensity of n-alkanes with more carbon atoms per molecule, the vicinity of the solid walls is preferentially adsorbed by longer alkanes (Castro et al, 1998;Harrison et al, 2014), thus leading to higher density crest in the near-wall region for the mixture with a greater proportion of heavier hydrocarbons. Because the bulk-fluid density of this composition is higher, however, the relative magnitude for adsorbed-and bulkphase density cannot be guaranteed to be larger.…”
Section: Effect Of Alkane Type On Adsorptionsupporting
confidence: 86%
See 1 more Smart Citation
“…For the composition with a higher percentage of methane, the fluctuation characteristics of the density profile compare well with results from previous studies related to pure methane adsorption (Ambrose et al, 2012;Liu et al, 2013;Mosher et al, 2013). Owing to the adsorption propensity of n-alkanes with more carbon atoms per molecule, the vicinity of the solid walls is preferentially adsorbed by longer alkanes (Castro et al, 1998;Harrison et al, 2014), thus leading to higher density crest in the near-wall region for the mixture with a greater proportion of heavier hydrocarbons. Because the bulk-fluid density of this composition is higher, however, the relative magnitude for adsorbed-and bulkphase density cannot be guaranteed to be larger.…”
Section: Effect Of Alkane Type On Adsorptionsupporting
confidence: 86%
“…For the first time, McGonigal et al (1990) directly imaged a two-dimensional, high-degree ordering of the alkane layer at the liquid/graphite interface using a scanning tunneling microscope (STM). Castro et al (1998) reported that longer alkane shows a strong preference for adsorption onto graphite, even when it has only one more -CH 2 group than the solvent and even if it is present only as the minor component. The suitability of Grand Canonical Monte Carlo (GCMC) simulation was examined by Do and Do (2005) to describe the adsorption of n-alkanes on graphitized thermal carbon black; they argued that if the carbon number of a given alkane is less than six, it can be modeled as a rigid molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Such a depression in melting point has been observed previously in adsorbed layers and in bulk alkane mixtures. 4,8 We attribute this broadening to the separation of the solidus and liquidus at this composition. The broadening in the peak remains on further addition of octane until a composition of 0.6È X oct \ 0.8 when the peaks narrow again, remaining narrow until the adsorbed layer is pure octane.…”
Section: Neutron DI †Ractionmentioning
confidence: 82%
“…4,8 We recently reported the adsorption behaviour of octane and nonane mixtures adsorbed on graphite at high (greater than monolayer) coverages.8 This work, combining calorimetry, incoherent and coherent neutron scattering, clearly indicated phase separation of the two components, that were simultaneously adsorbed in a solid monolayer that coexists with bulk solution. This phase separation arises because the two components have monolayers with di †erent space groups.…”
Section: Introductionmentioning
confidence: 97%
“…Previous calorimetry measurements on related systems indicate that the minimum amount required to have the characteristics of the true bulk solution phase is of the order of 5È10 monolayers. 10 Incoherent elastic neutron scattering is a powerful tool for the investigation of monolayers adsorbed from pure materials and solutions7,8 providing unambiguous information on both the state and absolute composition of an adsorbed layer and ¤ Contribution No. 6 from the Research Centre for Molecular Thermodynamics.…”
Section: Introductionmentioning
confidence: 99%